Loss of calcium-dependent protein kinases OsCPK5 and OsCPK13 leads to NLR-dependent resistance in rice - Zhanchun Wang; Shibo Yu; Wencai Xu; Han Peng; Xuan Zhou; Anja Liese; Lilan Chen; Guitao Zhong; Chen Zhong; Xianya Deng; Libo Han; Na Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Calcium (Ca 2+ ) signaling plays a crucial role in plant immunity, regulating both pattern-triggered immunity (PTI) through cell-surface receptors and effector-triggered immunity (ETI) via intracellular nucleotide-binding, leucine-rich repeat receptors (NLRs). Calcium-dependent protein kinases (CPKs/CDPKs) serve as key Ca 2+ sensors and signal transducers in these processes. In this study, we demonstrate the relevance of two rice CPKs, OsCPK5 and OsCPK13, for rice blast resistance. Both are Ca 2+ -responsive kinases, with potential in planta heteromer formation enhancing their phosphorylation/signaling functions. Single oscpk5 and oscpk13 mutants exhibit impaired early PTI responses and enhanced susceptibility to rice blast fungus, suggesting that these kinases are essential for effective immunity. Surprisingly, although it is also defective in PTI, the oscpk5 / 13 double mutant displays enhanced resistance to rice blast. An NLR protein OsCPK5/13-ASSOCIATING RESISTANCE PROTEIN 1 (OsCARP1), which is physically associated with both OsCPK5 and OsCPK13, is genetically required for the heightened resistance of oscpk5 / 13. Furthermore, OsCARP1-induced cell death in Nicotiana benthamiana can be suppressed by the expression of OsCPK5 and OsCPK13. Based on these findings, we postulate that the positive blast resistance roles of OsCPK5 and OsCPK13 are guarded by OsCARP1, thus leading to OsCARP1-dependent ETI resistance in the oscpk5 / 13 double mutant or upon manipulation by still unknown pathogen effectors during infection. Our results offer insights into how plants counteract potential pathogen attack on key Ca 2+ signaling immune components.